Remoção de quartzo grosso da carga circulante da flotação, por meio de peneiramento de alta frequência - Júlio César da Silva (2019)
Currently, the Minas / Rio system, owned by Anglo American, in its reverse cationic flotation concentration process has shown a considerably high accumulation of SiO2 >150µm in the flotation circulating load. This is mainly represented by the presence of quartz, which shows a rising trend along the time. The study aimed to evaluate the effect of the removal of coarse quartz particles through high frequency screening of the flotation circulating load. The study involved circulating load sampling campaigns, bench flotation tests, tests on Derrick and Metso pilot equipment, with variation of the main operating parameters of the equipment. Flotation circulating load samplings presented on average 46% of the retained mass at 150µm with 72% of the material related to quartz and only 4.0% related to Fe. Bench flotation tests with material extraction >150µm from the circulating load resulted in a decrease of approximately 1% of quartz in the final product, without reduction in metallurgical recovery. Screening tests on the 212µm produced undersizes with approximately 56% of Fe, with enrichment ratios of 1,49 tests at Metso and 1,36 tests at Derrick, with 95% metallurgical recovery. The oversizes presented approximately 6% of Fe. Mass balances resulted in a 0,18% of mass increase to a 25% of Fe circulating load content, with an annual production increase of approximately 88,000 tons of concentrate. For a 41% of Fe circulating load the result was even more significant, an increase of 0, 93% of mass recovery, with an annual production increase of approximately 322,000 tons. The study shows that the use of high frequency screen to remove large size quartz is a good alternative from a process perspective to maximize recoveries of Minas/Rio beneficiation project.